Childfree in Islamic Discourse: Analysis of Interpretation on QS. An-Nisa Verse 9 - Muhammad Abil Anam; Munasir Munasir (Journal of Islamic Studies and Education, 2025)
The childfree phenomenon is the existence of different views on the decision not to have children, both from a social, economic, and religious perspective. Childfree is considered an individual right that is influenced by factors of welfare, economic stability, and personal freedom. This study uses a qualitative method with a library research approach to analyze the concept of childfree in Islam, especially in relation to QS. An-Nisa verse 9. The findings of this research study are that the decision to be childfree in Islam has significant implications for the sustainability of Muslim generations, the inheritance of Islamic values, and the social and economic stability of the community. Islam emphasizes the importance of marriage and offspring as part of the maqashid sharia, with the aim of maintaining the existence and strength of the community. Classical scholars generally reject the decision to be childfree without sharia reasons, while contemporary scholars consider certain conditions that can justify it, such as health and economic factors.